Lost in the bloom: DNA-PKcs in green plants - Kumar, Koppolu Raja Rajesh (Frontiers in Plant Science, 2023)
The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is a protein encoded by the PRKDC gene in humans and plays a crucial role in repairing DNA double-strand breaks (DSBs). Recent studies have revealed that DNA-PKcs has additional functions in the cell beyond DSB repair, including transcriptional regulation, telomere protection and capping, preserving chromosomal integrity, and regulating senescence, apoptosis, and autophagy. Moreover, DNA-PKcs has also been implicated in regulating the innate immune response, and dysregulation of DNA-PKcs has been commonly observed in various types of cancers. Until recently it was believed that DNA-PKcs is not present in plants in general. However, DNA-PKcs is conserved in green plants ranging from microscopic green algae such as Ostreococcus of the chlorophytes to the tallest living trees on earth, Sequoia of the gymnosperms. Interestingly, DNA-PKcs has not been detected in angiosperms, or in basal angiosperms which are considered sister groups to all other flowering plants. The long polypeptide and gene length of DNA-PKcs coupled with errors in genome assembly, annotation, and gene prediction, have contributed to the challenges in detecting and extracting DNA-PKcs sequences in plant lineages. Sequence alignment showed that several amino acids throughout the length of DNA-PKcs are conserved between plants and human, and all the typical domains identified in human DNA-PKcs are also found in DNA-PKcs from green plants suggesting possible structural and functional conservation. Given the highly conserved nature of DNA repair pathways between mammals and plants further highlights the potential significance of DNA-PKcs in plant biology.